A Three-Year Retrospective Study on Survival of Ceramic-Veneered Zirconia (Y-TZP) Fixed Dental Prostheses Performed in Private Practices - Veronika Norström Saarva; Göran Bjerkstig; Anders Örtorp; Per Svanborg (International Journal of Dentistry)
Objectives. The aim of this retrospective study was to evaluate the three-year clinical outcome for ceramic-veneered zirconia fixed dental prostheses (FDPs). Methods. All patients who were treated with ceramic-veneered zirconia FDPs, in three private practices in Sweden, during the period June 2003 to April 2007 were included. Case records from 151 patients, treated with a total of 184 zirconia FDPs (692 units), were analysed for clinical data. All complications noted in the charts were registered and compared to definitions for success and survival and statistical analysis was performed using the Kaplan-Meier method and a Cox regression model. Results. In total, 32 FDPs in 31 patients experienced some type of complication (17.4% of FDPs, 20.5% of patients). Core fractures occurred in two (1.1%) FDPs. Two (1.1%) FDPs or 0.6% of units showed adhesive veneer fractures. Cohesive veneer fractures occurred in 10 (5.4%) FDPs (1.6% of units). The three-year cumulative success and survival rates (CSR) were 82.3% and 95.2%, respectively. Conclusions. Ceramic-veneered zirconia is a promising alternative to metal-ceramic FDPs, even in the posterior area. However, the higher survival rate of metal-ceramic FDPs should be noted and both dentists and patients must be aware of the risks of complications.